Should English Be a Primary School Compulsory Subject in Indonesia's Latest "Merdeka Belajar" Curriculum? - Rudha; Aulia Nisa' Khusnia (JELLT (Journal of English Language and Language Teaching), 2023)
The most recent Indonesian curriculum, Kurikulum Merdeka (Freedom Curriculum), permits the resumption of English instruction, when this kind of learning will be available, and how feasible it is for schools. This study aims to clarify, from the perspectives of the concerned parties, the importance of English Language topics in the Indonesian Primary School (PS) curriculum, which is confronted with the linguistic and political context in Indonesia (primary school EFL teachers, school principals, teacher educators, and parents). Twelve participants provided in-depth interview data for this study (two school principals, four English teachers, and six teacher educators). In addition to qualitative data, 73 enthusiastic parents provided quantitative survey data to assist this study. The grounded theory examined the relevancy of the data by analysing them. The results indicate that the implementation of English courses in the Indonesian PS curriculum is responsive to parental and societal needs. The most important outcome of this study is imperative for the inclusion of English courses in the PS curriculum, taking into account the Junior High School English standards, the demand in the global society, and English as an investment for the future, and the sooner, the better. This study also suggests teacher education preparation to identify the suitability of EFL teachers in PS and improve ELT policy at the primary level.